KONSELING BERBASIS PESANTREN UNTUK MEMPERKOKOH KARAKTER PELAJAR DALAM MENGHADAPI GLOBALISASI - Samsul Arifin (LP2M Universitas Ibrahimy, 2014)
Education, not only about learning but also about student development. The student development is counseling; a science that helps people to overcome problems and promote own potential (growth and development) for the better One of the attitudes required in building a civilization in globalization era is moderation. Boarding school appliedÂ moderate mindset, which is known as fikrah tawassuthiyyah; tawazun (balanced) and i'tidal (moderate).This paper describes the values of pesantren that can be absorbed in counseling techniques to change behavior. The research method use a qualitative approach type-hermeneutic ethnography. The data comes from documents and fieldnotes. The data analysis is data reduction, data display, and conclusion drawing.The results, the values that can be adapted is